METHOD OF CALCULATING THE OPTIMAL HEAT EMISSION GEOTHERMAL WELLS - A. I. Akaev; A. I. Ninalalov (Вестник Дагестанского государственного технического университета: Технические науки)
This paper presents a simplified method of calculating the optimal regimes of the fountain and the pumping exploitation of geothermal wells, reducing scaling and corrosion during operation. Comparative characteristics to quantify the heat of formation for these methods of operation under the same pressure at the wellhead. The problem is solved graphic-analytical method based on a balance of pressure in the well with the heat pump.